Peran Kepemimpinan Kiyai dalam Pengelolaan dan Pembentukan Karakter Santri di Pesantren - Masruroh, Masruroh; Tamyiz, Achmad; Shodiq, Arsyad; Muzahid, Hizbullah; Taufiqurrahman, Taufiqurrahman (TSAQOFAH, 2026)
This study is motivated by the limited number of works that specifically examine the multidimensional influence of kyai leadership in pesantren, despite the extensive literature on leadership in Islamic educational institutions more broadly. It aims to analyze the role of kyai leadership in shaping educational processes, institutional management, and the spiritual–moral character development of santri within the pesantren environment. A qualitative approach with a case study design was employed, involving 12 informants selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document analysis, and subsequently examined using thematic analysis. The findings indicate that kyai leadership is manifested in four main dimensions: spiritual leadership, moral guidance, institutional decision-making, and social–community relations. The kyai functions as a spiritual mentor, moral exemplar, strategic leader, and social mediator between the pesantren and the wider community. These results contribute to the development of Islamic leadership theory and deepen understanding of pesantren governance. The study concludes that integrative kyai leadership is crucial in determining the identity, sustainability, and educational effectiveness of pesantren. The recommendations include strengthening leadership regeneration, enhancing managerial capacity, and building collaborative networks, while future research may explore the transformation of leadership in modern pesantren and the adaptation of traditional authority within contemporary educational contexts.